Hemoglobin‐Related Biomaterials and their Applications. Issue 3 (23rd December 2022) - Li, Shaobing; Sun, Wei; Ouyang, Min; Yu, Bo; Chen, Yan; Wang, Yupeng; Zhou, Dongfang
Abstract : Hemoglobin (Hb) is a physiological oxygen‐transport metalloprotein present in the red blood cells. With the in‐depth study, many functions of Hb are developed, and kinds of Hb‐related biomaterials are applied for biomedical therapeutics in the past decades. Herein, the recent advances of Hb‐related biomaterials and their applications, including the clinical progress of Hb‐based oxygen carriers (HBOCs) as blood substitutes, and the applications in the field of tumor therapy, wound healing, and anti‐inflammation therapy through utilizing its function of multiple gas delivery (O2, CO, NO), peroxidase‐like catalysis, and targeting macrophage, are summarized. With the rapid development of science and technology, more versatile Hb‐related biomaterials are designed in the future for other applications. Abstract : Recent advances of hemoglobin‐related biomaterials and their applications in blood substitutes, antitumor therapy, wound healing, and anti‐inflammation therapy are summarized.